Biodiversity in Nicaragua: A country Study - Ministry of the Environment and Natural Resources (Nicaragua: MARENA, 2000)
But there are resources available that discuss the biodiversity of the country.
1. Diversity of Ecosystems 2. Organization of the study
incluye índice
Col. Agro
Keywords: 1. LAND USE AND PRODUCTION 2. CULTURAL DIVERSITY